Langmuir and Langmuir-Blodgett films of poly[2-methoxy-5-(n-hexyloxy)-p-phenylenevinylene] - Ferreira, M.; Constantino, CJL; Olivati, C. A.; Vega, A. L.; Balogh, D. T.; Aroca, R. F.; Faria, R. M.; Oliveira, O. N. (Amer Chemical Soc, 2003)
Langmuir films have been fabricated from poly[(2-methoxy-5-n-hexyloxy)-p-phenylenevinylene] (OC1OC6-PPV). The stability and the area per monomer for condensed films indicate the formation of true monolayers with a very small extent of aggregation, which is unusual for polymer films. This is attributed to the linearity of the alkyl side chain. The Y-type Langmuir-Blodgett (LB) films produced from Langmuir films of OC1OC6-PPV have distinctive features compared to those of cast films, probably due to the organization in the LB films whereas the molecules are randomly oriented in cast films. Infrared absorption spectra recorded for both transmission and reflection modes indicate that OC1OC6-PPV molecules are anchored to the substrate by the lateral groups. This is confirmed by the Raman spectrum, in which a distortion of the vinylene group was observed, and by surface enhanced fluorescence (SEF) on an LB monolayer deposited onto Ag nanoparticles. The more homogeneous nature of the LB films in comparison with the case of cast films was demonstrated by optical microscopy and fluorescence measurements where the emission spectra were essentially the same for different regions of an LB film but showed dispersion in cast films. The LB films also displayed reversible photoconductivity.